Assessment Of Horizontal Migration Behavior Of Light Non-Aqueous Phase Liquid (Lnapl) At Capillary Fringe Due To Fluctuating Groundwater Table And Precipitation - Rashid, Anis Adriana Mohd (Universiti Sains Malaysia, 2022)
When the LNAPL reach to the subsurface of different environment, it is very complex to determine the migration behavior of LNAPL. Therefore, to have a clear understanding and better remediation efficiency, 2D tank experiments were conducted to study the lateral and horizontal migration of LNAPL with the effect of groundwater fluctuation and precipitation intensity. Simplified Image Analysis Method (SIAM) was adopted in this study to determine the saturation distribution of LNAPL and water in the 2D tank with different types of groundwater fluctuation, fixed LNAPL volume and the precipitation intensity. In saturation of water under high groundwater tables fluctuation with the effect of precipitation, the water saturation increased with the effect of precipitation while during the drainage stage, the water saturation experience significant decreased. When LNAPL migration behaviour under high groundwater tables, it can be observed that the LNAPL saturation at 40 cm increased to around 22%, while at water table, it dropped to 12%. The LNAPL at 40 cm only fall about 7% and this condition can be described by the entrapped diesel within the soil pores. For the vertical migration behaviour of LNAPL, it can be observed that the LNAPL saturation increased to 6% and increased more during the next hour of precipitation stage. Other than that, the saturation of diesel increased in the capillary fringe zone because the diesel tends to migrate deeper with the help of gravitational force. For the lateral migration, it can be observed that the LNAPL saturation increased at 28 cm, 31 cm and 38 cm around 11%, 6% and 4% respectively. After the precipitation stage, it can be observed that the LNAPL saturation increased back for all the 3 different elevation mentioned above. The LNAPL saturation remained higher after the drainage to 28 cm because the risen of the water table pushed up the accumulated diesel at 28 cm elevation to float along new capillary fringe.